Effect of Cooking Method on Vitamin C Loses and Antioxidant Activity of Indigenous Green Leafy Vegetables Consumed in Western Uganda - Hellen W. Kinyi; Michael Tirwomwe; Herbert Izo Ninsiima; Conrad O. Miruka (International Journal of Food Science)
Indigenous green leafy vegetables are known to contain high levels of antioxidants and are recommended in the management of chronic diseases. However, their consumption has received lower patronage. This is partly attributed to farmers replacing the growing of indigenous green leafy vegetables with their exotic counterparts and scarce information on their nutritional benefits. This study explored the effect of cooking methods (boiling and steaming for 10 minutes) on the antioxidant activity of Amaranthus dubius, Solanum nigrum, and Curcubita maxima. Spectrometry was used to evaluate the reducing power and antihemolytic activity. Titration via the 2,6-indophenol method was used for measuring vitamin C and replacement titration for hydrogen peroxide scavenging activity. Cooking the vegetables by steaming or boiling caused up to 99% reduction in the vitamin C concentration of the cooked vegetables. The antioxidant activity of the cooked vegetables varied across the species assessed and cooking method used. Steaming retained and in some instances promoted the antioxidant activity of the vegetables. The study concludes that cooking by either steaming or boiling alters the antioxidant activity of indigenous vegetables.